EKSISTENSI MEDIASI DAN HAKAM DALAM TINJAUAN HUKUM ACARA PERADILAN AGAMA - Marwing, Anita (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2012)
The breakdown of marriage can actually be minimized by peace, as enshrined in the principles of procedural law, namely the principle of religious courts must reconcile the more complete set in Article 65 and 82 of Law No. 7 Year 1989 On the Religious. The process is known and efforts to reconcile with the mediation process. Article 76 of Law Number 7 Year 1989 jo. Law No. 3 of 2006 jo. Act No. 50 of 2009 has established the existence of Hakam in existence similar to divorce mediator. On the other hand, raised the question of imposing a mediation in divorce cases that have dilegalformalkan with Perma No. 1 of 2008 on Mediation Procedures in court, while Hakam as part of the procedural law is legitimized in advance rather than mediation. Writing is how the existence of Hakam and mediation in the judicial review court proceedings religion.